Long‐term disease‐free survival in a patient with cerebral recurrence from adenocarcinoma of the fallopian tube. Issue 9 (2nd July 2013) - Shimada, Chisa; Todo, Yukiharu; Minobe, Shinichiro; Okamoto, Kazuhira; Kato, Hidenori
Abstract Cerebral recurrence from Müllerian cancer is a rare event and prognosis of patients with such a condition is poor. We report a case of cerebral recurrence from International Federation of Gynecology and Obstetrics classification stage IV tubal cancer presenting with inguinal lymphadenopathy. The patient achieved more than 7 years' disease‐free survival after irradiation to the brain despite the inauspicious event. The present case had a rare clinical course in terms of primary site, primary symptom, failure site, and clinical outcome. Patients with brain metastasis from Müllerian cancer have a chance for long‐term survival under specified circumstances, such as solitary metastasis, no extracranial metastasis, no recurrence preceding brain metastasis and small tumor size.